Determinan Produktivitas Kerja Karyawan pada Industri Coffee Shop: Pendekatan Terintegrasi Faktor Psikologis, Fisiologis, dan Lingkungan Kerja - Fadli Masuri; Ariawan Ariawan; Moh. Akhtar SRED (Journal of Management and Creative Business, 2026)
This study examines the effects of psychological, physiological, and environmental factors on employee work productivity at Warung Kopi Ahzahra Makassar. A quantitative approach with an associative research design was employed. The sample consisted of 52 respondents selected through simple random sampling from a population of 109 employees. Data were collected using a structured questionnaire and analyzed through multiple linear regression using IBM SPSS Statistics. The results indicate that psychological factors (β = 0.491, p < 0.001), physiological factors (β = 0.611, p = 0.001), and environmental factors (β = 1.182, p < 0.001) have positive and significant effects on employee work productivity, with environmental factors emerging as the most dominant predictor. Simultaneously, the three independent variables significantly influence work productivity (F = 39.412, p < 0.001), explaining 71.1% of the variance (R² = 0.711). The study concludes that improving employee work productivity requires an integrated approach encompassing psychological well-being, physical health, and a supportive work environment. Therefore, organizations should prioritize employee well-being and workplace conditions to achieve sustainable productivity improvement.